Pemaafan Sebagai Metode Para Santri Antisipasi Kasus Bullying di Pondok Pesantren - Abdusshomad, Alwazir (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic boarding school is a traditional Islamic educational institution in Indonesia. Cases of bullying in Islamic boarding schools are a problem that often occurs. Bullying can be in the form of bad treatment, such as intimidation, ridicule, physical violence, or discrimination against other students. From previous research it is known that there are internal and external aspects that cause bullying. Bullying can lead to negative consequences for students who become victims, such as psychological or mental health problems. The author wishes to continue discussing other aspects of the occurrence of bullying and seek alternative methods so that they can be used to anticipate bullying cases at Islamic boarding schools. Library research is used in this article. The results of this study are that there are three kinds of motivation that may arise from victims of bullying, namely revenge, avoidance and making up. Bullying can cause very strong feelings for victims, including resentment. Revenge can be interpreted as a feeling of wanting to get back at the bully. So that revenge can be concluded can lead to repetition of bullying behavior in the future. Forgiveness is useful for overcoming feelings of anger, hatred, or revenge that victims may have against perpetrators who have bullied them. Forgiveness can help students at Islamic boarding schools to let go of these negative feelings and make them feel better. Forgiveness can also help to improve relationships with others and increase emotional and physical happiness